PENINGKATAN PROSES PEMBELAJARAN TEMATIK DENGAN MENGGUNAKAN PENDEKATAN PROBLEM BASED LEARNING DI KELAS III SD: (Enhancing the Learning Process by Using Thematic Problem Based Learning In Class III Elementary School) - Vivi Puspita; Nofri Yuhelman (UIR Press, 2017)
Learning is a process of interaction between teacher-student as reciprocal communication conducted on the educational situation to achieve a goal. Learning in the lower class do thematically so that meaningful learning. Thematic is a concept of learning by using themes to link several subjects, one concept to another and between the subject to spontaneous or planned either in one or more subject areas and with diverse experience. As an effort to improve the learning process can be done by using problem-based learning, ie learning by presenting contextual issues to facilitate students build knowledge independently or groups. This type of research is a classroom action research using qualitative and quantitative approaches. procedures covering the research, planning, implementation, monitoring / observation, and reflection. The research data in the form of information about the increase of learning in this case reciprocal activity between teachers and students. The research was conducted by two cycles.